Spatio-temporal dynamics of neotropical high-altitude mixed oak forests in western Mexico - Olvera Vargas, M; Olvera Vargas, Miguel (2006)
﻿ This thesis contributes to the understanding of two of the most intriguing questions that forest ecologists have faced over recent decades: 1) how high diversity is maintained in species-rich ecosystems; and 2) what is the role of spatio-temporal environmental variation in structuring forest communities. The aims of the research were to ascertain how species composition varies both spatially and temporally and how changes in the vegetation can be understood in the context of species coexistence theories (niche versus neutral). A group of 38 sympatric species, including 9 species of Quercus, on which little ecological research has been undertaken, were used in this study. The data used in this project include eleven years of periodic remeasurements of permanent plots established in high-altitude oak forests in Mexico. Adult, sapling and seedling trees were studied as well as their environmental surrounding. Spatial and temporal variations in forest composition were analysed using multivariate statistical approaches. The results show that there are discrete communities in these mixed oak forests that correspond to specific environments. At a broad scale the study area can be classified into two floristic zones, a mesic zone characterised by associations that include Quercus candicans, Q. laurina and Q. castanea and; a xeric zone dominated by Q. crassipes. However of a finer scale of analysis important variation in composition was associated with different life stages of the trees, with adult trees showing much stronger environmental associations than seedlings and saplings. Successional pathways and rates vary at relatively fine scales. This may be as a result of dominance alternation between dominant canopy species. Micro-niche zonation processes caused by a high degree of environmental heterogeneity combined with individual species traits explain the coexistence of phylogenetically similar sympatric Quercus species. A hierarchy of processes, each acting at a different spatial and temporal scale, determines species diversity and coexistence. The overall findings support the idea that niche differentiation rather than chance events such as dispersal limitation, are more important in permitting species coexistence.